2019
DOI: 10.1007/s11854-019-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy bounds for the distribution of the Riemann zeta-function and applications

Abstract: We investigate the distribution of the Riemann zeta-function on the line Re(s) = σ. For 1 2 < σ ≤ 1 we obtain an upper bound on the discrepancy between the distribution of ζ(s) and that of its random model, improving results of Harman and Matsumoto. Additionally, we examine the distribution of the extreme values of ζ(s) inside of the critical strip, strengthening a previous result of the first author.As an application of these results we obtain the first effective error term for the number of solutions to ζ(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 16 publications
6
52
0
Order By: Relevance
“…We prove the following estimate in this section. The proof is based on the method in Section 5 of [14]. Proposition 6.2.…”
Section: Proof Of Theorem 16mentioning
confidence: 99%
“…We prove the following estimate in this section. The proof is based on the method in Section 5 of [14]. Proposition 6.2.…”
Section: Proof Of Theorem 16mentioning
confidence: 99%
“…holds for any 1/2 < σ 1 ≤ σ 2 and some nonnegative continuous function g(σ). By a straightforward adaptation of [7], the author in [9] improved the above asymptotic formula to…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lamzouri, Lester and Radziwiłł [7] reduced the size of the error in (1) and proved that N a (σ 1 , σ 2 ; T ) = c(a, σ 1 , σ 2 )T + O T log log T (log T ) σ 1 /2 holds for fixed 1/2 < σ 1 < σ 2 < 1 and T ≥ 3.…”
Section: Introductionmentioning
confidence: 99%
“…is small for σ = σ T , where the supremum is taken over all rectangular regions in the complex plane with their sides parallel to real or imaginary axis. Bounding the discrepancy has been studied by various authors (e.g., [5], [7]). In particular, Lamzouri et al [7,Theorem 1.1] showed that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation